2017
DOI: 10.1017/s026646741700030x
|View full text |Cite
|
Sign up to set email alerts
|

Browsing and plant traits in nutrient-rich and nutrient-poor savannas in Tanzania

Abstract: Abstract:Environmental productivity is important in determining defensive or tolerance traits of plants, with nutrient-rich savannas showing tolerance and nutrient-poor showing defence traits. Animals are affected differently by such traits due to differences in size, and other characters. We studied differences in browsing as a response to plant traits by elephant, giraffe and impala in Mikumi, a nutrient-poor savanna, and Serengeti, a nutrient-rich savanna, both in Tanzania, for a total of 4 mo; 2 mo at each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…The GSE is characterized by two major seasons: a dry season extending from June to October and a wet season extending from November to May (Mmassy, Fyumagwa, Bevanger, & Røskaft, 2018). Rainfall is bimodal; the short rains from November to February and the long rains from April to June, and mean annual rainfall of 600-1,200mm (Mramba, Andreassen, & Skarpe, 2017;Mmassy et al, 2018). The mean monthly maximum and minimum temperatures in the western Serengeti fluctuate between 25°C-32°C and 13°C-19°C, respectively (Campbell & Hofer, 1995).…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…The GSE is characterized by two major seasons: a dry season extending from June to October and a wet season extending from November to May (Mmassy, Fyumagwa, Bevanger, & Røskaft, 2018). Rainfall is bimodal; the short rains from November to February and the long rains from April to June, and mean annual rainfall of 600-1,200mm (Mramba, Andreassen, & Skarpe, 2017;Mmassy et al, 2018). The mean monthly maximum and minimum temperatures in the western Serengeti fluctuate between 25°C-32°C and 13°C-19°C, respectively (Campbell & Hofer, 1995).…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…The GSE is a highland savannah region with plains and woodlands at an altitude of 1,000-1,800m above sea level. The area receives two rainy seasons; the short rains which normally start in late November to February and the long rains from March to May, with an average of annual rainfall ranging from 600 to 1,100mm (Mramba et al, 2017). The mean annual temperature fluctuates with minimum range of 13 to 19°C and maximum of 25 to 32°C (Campbell & Hofer, 1995).…”
Section: Study Areamentioning
confidence: 99%
“…For instance, the presence of E. tenuifolia, C. dactylon, and C. gayana influenced the occurrence of grazers like zebras, antelopes, hartebeests as well as generalists like the elands. Other studies have reported that plant species drive the occurrence of the mammalian herbivores in a particular locality by providing the much-needed food to the animals [37,15]. In most cases, the mammalian herbivore grazers and browsers were seen foraging together among the park's grasses and herbs.…”
Section: Discussionmentioning
confidence: 99%